2019
DOI: 10.1111/hdi.12735
|View full text |Cite
|
Sign up to set email alerts
|

Atypical posterior reversible encephalopathy syndrome in a noncompliant hemodialysis patient: Case report and literature review

Abstract: Posterior reversible encephalopathy syndrome (PRES) is a reversible vasogenic brain edema in patients who present with seizure, headache, visual disturbance, and altered mental status, and a characteristic neuroimaging profile. Although PRES predominantly affects the bilateral parieto‐occipital areas, involvement of the frontal and temporal lobes, basal ganglia, brainstem, and cerebellum is not uncommon. Isolated involvement of the brainstem and cerebellum sparing the parieto‐occipital lobe is rarely reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…She had missed three dialysis sessions which likely contributed to her presentation. Renal failure is one of the most common causes of PRES and isolated brainstem and cerebellar PRES has been reported in patients non-adherent to hemodialysis [ 1 , 5 , 7 ]. A recently published study also found that majority of patients presenting to the emergency department with PRES were hypertensive similar to the patient described in this case [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…She had missed three dialysis sessions which likely contributed to her presentation. Renal failure is one of the most common causes of PRES and isolated brainstem and cerebellar PRES has been reported in patients non-adherent to hemodialysis [ 1 , 5 , 7 ]. A recently published study also found that majority of patients presenting to the emergency department with PRES were hypertensive similar to the patient described in this case [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posterior reversible encephalopathy syndrome (PRES) represents a neurological disorder with varied clinical presentation and typical imaging findings. Numerous triggering-factors are prevalent among end-stage renal disease (ESRD) population: arterial hypertension, volume-overload, uremia, transplantation, autoimmune and hematological diseases, (pre)eclampsia, infection, electrolyte disturbances, medication [immunosuppressants, chemotherapy, erythropoietin stimulating agents (ESA)] [1][2][3][4][5]. Clinical manifestations depend on the involved region(s) of the brain [1].…”
Section: Introductionmentioning
confidence: 99%